Molecular mechanism of Mad1 kinetochore targeting by phosphorylated Bub1. (19th May 2021) - Fischer, Elyse S; Yu, Conny W H; Bellini, Dom; McLaughlin, Stephen H; Orr, Christian M; Wagner, Armin; Freund, Stefan M V; Barford, David
Abstract: During metaphase, in response to improper kinetochore‐microtubule attachments, the spindle assembly checkpoint (SAC) activates the mitotic checkpoint complex (MCC), an inhibitor of the anaphase‐promoting complex/cyclosome (APC/C). This process is orchestrated by the kinase Mps1, which initiates the assembly of the MCC onto kinetochores through a sequential phosphorylation‐dependent signalling cascade. The Mad1‐Mad2 complex, which is required to catalyse MCC formation, is targeted to kinetochores through a direct interaction with the phosphorylated conserved domain 1 (CD1) of Bub1. Here, we present the crystal structure of the C‐terminal domain of Mad1 (Mad1 CTD ) bound to two phosphorylated Bub1 CD1 peptides at 1.75 Å resolution. This interaction is mediated by phosphorylated Bub1 Thr461, which not only directly interacts with Arg617 of the Mad1 RLK (Arg‐Leu‐Lys) motif, but also directly acts as an N‐terminal cap to the CD1 α‐helix dipole. Surprisingly, only one Bub1 CD1 peptide binds to the Mad1 homodimer in solution. We suggest that this stoichiometry is due to inherent asymmetry in the coiled‐coil of Mad1 CTD and has implications for how the Mad1‐Bub1 complex at kinetochores promotes efficient MCC assembly. Synopsis: Activation of the mitotic checkpoint complex (MCC) is orchestrated by a sequential phosphorylation‐dependent signalling cascade. This study reveals the molecular mechanism for kinetochore targeting of the Mad1‐Mad2 complex. The crystal structure of the C‐terminal domain of Mad1 (Mad1 CTD ) bound to phosphorylated Bub1 CD1 peptides explains how phosphorylation creates a direct interaction with Mad1 CTD . Bub1 CD1 pThr461 not only directly interacts with Arg617 of the conserved RLK motif of Mad1 CTD but also stabilizes the Bub1 CD1 helix dipole. In solution only one Bub1 CD1 binds to the Mad1 homodimer. Inherent asymmetry within Mad1 CTD likely controls Bub1 binding and stoichiometry. Abstract : Activation of the mitotic checkpoint complex (MCC) is orchestrated by a sequential phosphorylation‐dependent signalling cascade. This study reveals the molecular mechanism for kinetochore targeting of the Mad1‐Mad2 complex.